2010
DOI: 10.1177/1557988310377926
|View full text |Cite
|
Sign up to set email alerts
|

“It Used to Be That if It Weren’t Broken and Bleeding Profusely, I Would Never Go to the Doctor”: Men, Masculinity, and Health

Abstract: Masculine gender scripts have been influential in health decision making in men. In addition, although past research has identified some success in using churches as sites for health education with women, little is known if similar programs would be successful with men. It is also unclear if religious beliefs influence the health attitudes and behaviors of men. Four focus groups with men from four religious denominations were conducted to learn about their health beliefs, attitudes, and behaviors, with the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…Other methods that were used in articles were focused groups, interviews, and surveys. Focus groups were used to combine grounded theory in order to discover common themes of men's beliefs that influence health attitudes and health behaviors (Gast and Peak ). Similarly, Hunter and associates () used open‐ended question interviews to explore themes of health behaviors perceptions from (among others) Hispanic men.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other methods that were used in articles were focused groups, interviews, and surveys. Focus groups were used to combine grounded theory in order to discover common themes of men's beliefs that influence health attitudes and health behaviors (Gast and Peak ). Similarly, Hunter and associates () used open‐ended question interviews to explore themes of health behaviors perceptions from (among others) Hispanic men.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Hunter and associates () used open‐ended question interviews to explore themes of health behaviors perceptions from (among others) Hispanic men. Both studies used some measure of community involvement to recruit their participants through churches (Gast and Peak ) and community civic‐based organizations (Hunter et al ). Gast and Peak specifically stated that “the men in the focus groups were engaged and forthcoming with their input and ideas about men's health both in terms of personal needs and community programming” ( p. 322).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, men are less likely to seek help for medical concerns (Banks, 2001; Department of Health and Human Services [DHHS], 1998;Husaini, Moore, & Cain, 1994;Wills & DePaulo, 1991). Men visit their medical providers less frequently and engage in fewer preventative care measures than women (Courtenay, 2000;Gast & Peak, 2011). They often wait until a disease has progressed or physical symptoms are present prior to seeking-help (Francome, 2000).…”
Section: Men and Help-seekingmentioning
confidence: 99%
“…Previous research on masculinity and health beliefs supports that men do not discuss health issues unless they are serious and solvable and that men are averse to disclosing vulnerability (Verdonk, Seesing, & de Rijk, 2010). Gast and Peak (2011) reported that men are willing to discuss health concerns but that male-friendly health education programs are needed because men may not feel comfortable with the way services are currently delivered. Men's Sheds represent a novel approach to enhancing the health of men in Australia by providing a male-friendly space and should be investigated for use with older men in the United States (Ballinger, Talbot, & Verrinder, 2009).…”
Section: Strategies Suggested To Increase Male Participationmentioning
confidence: 99%